2022
DOI: 10.3389/fmicb.2022.1007609
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhea with deficiency kidney-yang syndrome caused by adenine combined with Folium senna was associated with gut mucosal microbiota

Abstract: The present study aims to study and analyze the characteristics of gut mucosal microbiota in diarrhea mice with deficiency kidney-yang syndrome. Ten male mice were randomly divided into the control group and the model group. Diarrhea mice model with deficiency kidney-yang syndrome was established by adenine combined with Folium sennae. The kidney structure was observed by hematoxylin-eosin (HE) staining. Serum Na+-K+-ATP-ase and Ca2+-Mg2+-ATP-ase were detected by enzyme-linked immunosorbent assay (ELISA). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
(42 reference statements)
0
14
0
Order By: Relevance
“…Additionally, its strong reproducibility enables consistent replication across different research laboratories, enhancing the reliability and comparability of research ndings [15] . Administering speci c drugs, adenosine, to in uence kidney function and induce experimental animals into a state of Kidney De ciency is currently a primary method for generating infertility [16][17] . On one hand, adenosine possesses reproductive function impairing effects, simulating the impact of purine metabolism disruptions on kidney function, effectively replicating the physiological characteristics of Kidney De ciency.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, its strong reproducibility enables consistent replication across different research laboratories, enhancing the reliability and comparability of research ndings [15] . Administering speci c drugs, adenosine, to in uence kidney function and induce experimental animals into a state of Kidney De ciency is currently a primary method for generating infertility [16][17] . On one hand, adenosine possesses reproductive function impairing effects, simulating the impact of purine metabolism disruptions on kidney function, effectively replicating the physiological characteristics of Kidney De ciency.…”
Section: Introductionmentioning
confidence: 99%
“…By dissecting the statistically modulated species (Fig. 5b-g), we found that TNBS colitis associated with an expansion of Bacteroides thataiotaomicron 40 , Bacteroides acidifaciens, Enterococcus faecalis 41–44 , Enterococcus gallinarum 45 , Erysipellatoclostridium cocleatum 46,47 , Lactobacillus animalis, Lactobacillus murinus, Ruminococcus flavefaciens 48 , Escherichia coli 45 , Shigella flexneri 4951 and Akkermansia muciniphila 52–54 known to be related to pathogenesis of human IBD and experimental murine colitis. In addition, the development of TNBS colitis associated with a decreased abundance of Clostidium sp 55 , Clostridium fusiformis , Eubacterium plexicaudatum 56 and Marvinbryantia formatexigens .…”
Section: Resultsmentioning
confidence: 99%
“…Diarrhea is closely related to intestinal microbiota disorder and intestinal mucosal barrier injury. Diarrheal mice had decreased intestinal microbiota diversity, increased inflammatory factors, decreased secretive immunoglobulin A (sIgA), abnormal energy metabolism, increased harmful intestinal bacteria, and decreased beneficial bacteria [ 15 , 16 ]. Impairment of intestinal mucosa integrity increased inflammatory factors and destruction of the intestinal mucosal barrier in diarrhea patients [ 17 ].…”
Section: Introductionmentioning
confidence: 99%